FEATURES OF THE COURSE OF HYPERTENSION IN PATIENTS WITH RHEUMATIC ARTHRITIS - Khalimova Kholida Khakimboevna; Salaeva Muborak Saidobdullaevna (Journal Park Publishing, 2022)
Currently, there is a large growth of comorbid diseases that weigh down the process how twat diseases. Long -term therapy of rheumatoid arthritis adversely affects the course of hypertension.
Keywords: hypertension, rheumatoid arthritis, comorbidity.